The Evaluation of Glioblastoma Cell Dissociation and Its Influence on Its Behavior - Skarkova, Veronika; Krupova, Marketa; Vitovcova, Barbora; Skarka, Adam; Kasparova, Petra; Krupa, Petr; Kralova, Vera; Rudolf, Emil (International journal of molecular sciences, 2019)
PURPOSE: Primary cell lines are a valuable tool for evaluation of tumor behavior or sensitivity to anticancer treatment and appropriate dissociation of cells could preserve genomic profile of the original tissue. The main aim of our study was to compare the influence of two methods of glioblastoma multiforme (GBM) cell derivation (mechanic-MD; enzymatic-ED) on basic biological properties of thus derived cells and correlate them to the ones obtained from stabilized GBM cell line A-172. METHODS: Cell proliferation and migration (xCELLigence Real-Time Cell Analysis), expression of microRNAs and protein markers (RT-PCR and Western blotting), morphology (phase contrast and fluorescent microscopy), and accumulation of temozolomide (TMZ) and its metabolite 5-aminoimidazole-4-carboxamide (AIC) inside the cells (LC-MS analysis) were carried out in five different samples of GBM (GBM1, GBM2, GBM32, GBM33, GBM34), with each of them processed by MD and ED types of isolations. The same analyses were done in the A-172 cell line too. RESULTS: Primary GBM cells obtained by ED or MD approaches significantly differ in biological behavior and properties of these cells. Unlike in primary MD GBM cells, higher proliferation, as well as migration, was observed in primary ED GBM cells, which were also associated with the acquired mesenchymal phenotype and higher sensitivity to TMZ. Finally, the same analyses of stabilized GBM cell line A-172 revealed several important differences in measured parameters. CONCLUSIONS: GBM cells obtained by MD and ED dissociation show considerable heterogeneity, but based on our results, MD approach should be the preferred method of primary GBM cell isolation.
Keywords: cell isolation; nádory mozku; Drug Screening Assays, Antitumor; regulace genové exprese u nádorů; Humans; Tumor Cells, Cultured; Brain Neoplasms; alkylační protinádorové látky; glioblastoma multiforme; separace buněk; lidé; chemorezistence; proliferace buněk; glioblastom; nádorové buňky kultivované; Antineoplastic Agents, Alkylating; pohyb buněk; Cell Proliferation; Cell Movement; Cell Separation; Temozolomide; screeningové testy protinádorových léčiv; nádorové buněčné linie; temozolomide; Glioblastoma; temozolomid; Cell Line, Tumor; Gene Expression Regulation, Neoplastic; resistance; Drug Resistance, Neoplasm